Advances in Electrical Engineering and Automation - Xie, Anne; Huang, Xiong (Advances in Intelligent and Soft Computing, 2012)
EEA2011 is an integrated conference concentration its focus on Electrical Engineering and Automation. In the proceeding, you can learn much more knowledge about  Electrical Engineering and Automation of researchers from all around the world. The main role of the proceeding is to be used as an exchange pillar for researchers who are working in the mentioned fields. In order to meet the high quality of Springer, AISC series, the organization committee has made their efforts to do the following things. Firstly, poor quality paper has been refused after reviewing course by anonymous referee experts. Secondly, periodically review meetings have been held around the reviewers about five times for exchanging reviewing suggestions. Finally, the conference organizers had several preliminary sessions before the conference. Through efforts of different people and departments, the conference will be successful and fruitful.  .